Verbal behaviour as an indicator of personnel wellbeing - T. S. Putilovskaya; G. M. Kassymova; E. V. Zubareva (Цифровая социология)
The article examines one of the possible applications of speech activity theory and the text psychological structure as the product of this activity to the research of personnel wellbeing. Very often, an employee’s wellbeing status is inaccessible to management. The idea is that the verbal behaviour psychological pattern can be used as an indicator of employee wellbeing status perception. The authors’ aim was to develop a text analysis model to be used for revealing the peculiarities of wellbeing perception status; to determine the most diagnostic parameters of the model; and to apply them to the personnel wellbeing assessment. The authors’ conclusions are based on analyzing numerous personnel speech samples, which show how the model functions as an instrument for measuring the real quality of wellbeing status perception and how diagnostic the proposed model parameters are. The research of speech samples, which belong to university foreign language trainers from Russia and Kazakhstan, allows us to describe a typical teacher who is not satisfied with career opportunities available, the level of salary and constant management pressure. The results of the study can be applied to practical human resource management and the development of new ways of motivating and training employees in any professional field.